Educating epistemological principles, virtues and research skills. Review on Marina Klimenko’s textbook “Research Methods in the Social Sciences”: Book review of: Marina Klimenko (Dept. of Psychology, University of Florida), “Research Methods in the Social Sciences”, William England Sentia Publishing 2020 - Nowak, Ewa (Filozofia Publiczna i Edukacja Demokratyczna, 2021)
proving university students’ research skills, research integrity and best standards for scientific excellence is crucial for all disciplines. Marina Klimenko, a senior lecturer at the University of Florida, developed an innovative digital textbook entitled Research Methods in the Social Sciences (2020) with the focus on investigative psychology. The edition was powered by the e-learning portal and published by Sentia Publishing. The author’s own epistemological and research expertise is combined here with her competence in higher education didactics. Klimenko’s textbook seems to be perfectly tailored for prospective researchers – and useful for various disciplines representing the social sciences and humanities.